2016
DOI: 10.1038/srep31386
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of unique ligand specificity of KAI2-like protein from parasitic weed Striga hermonthica

Abstract: The perception of two plant germination inducers, karrikins and strigolactones, are mediated by the proteins KAI2 and D14. Recently, KAI2-type proteins from parasitic weeds, which are possibly related to seed germination induced by strigolactone, have been classified into three clades characterized by different responses to karrikin/strigolactone. Here we characterized a karrikin-binding protein in Striga (ShKAI2iB) that belongs to intermediate-evolving KAI2 and provided the structural bases for its karrikin-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(96 citation statements)
references
References 45 publications
13
83
0
Order By: Relevance
“…A very interesting structural insight of ligand specificity in KAI2 has been recently reported. Xu et al () identified an intermediate‐evolving KAI2, KAI2iB in Striga hermonthica . This receptor specifically bound KAR and not SL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very interesting structural insight of ligand specificity in KAI2 has been recently reported. Xu et al () identified an intermediate‐evolving KAI2, KAI2iB in Striga hermonthica . This receptor specifically bound KAR and not SL.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in the formation of a smaller closed pocket solely responsible for the selective binding of KAR. Furthermore, some non‐conserved amino acids were also found to mediate the unique ligand binding profile of KAI2iB in S. hermonthica and the exertion of evolutionary forces on these residues possibly led to the diversification of KAI2 receptors (Xu et al ). Bythell‐Douglas et al () phylogenetically analyzed 339 members of the D14/KAI2 family from land plants and charophyte algae.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies have demonstrated that D14 is activated by covalent modification of the catalytic triad following SL hydrolysis (Zhao et al, 2013; de Saint Germain et al, 2016; Yao et al, 2016), confirming D14 as a SL receptor (Hamiaux et al, 2012). Several reports have also demonstrated interaction of KAR with Arabidopsis KAI2 and its homologs (Guo et al, 2013; Kagiyama et al, 2013; Xu et al, 2016), but no covalent interaction has been reported. Additional butenolides such as synthetic SL isomer GR24 ent -5DS also activate KAI2 signaling, while mutation of the catalytic triad abolishes hydrolysis and signaling (Scaffidi et al, 2014; Waters et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…KAI2 is an active hydrolase, and mutagenesis of the catalytic triad renders it inactive both in vitro as an enzyme and in planta as a signal transducer (Waters et al 2015a(Waters et al , 2015b. Several studies have detected direct interaction between KAR 1 and KAI2 homologues using isothermal calorimetry and/or fluorescence-based binding assays (Guo et al 2013;Kagiyama et al 2013;Xu et al 2016). Two of these studies have also used crystallography to determine the position of KAR 1 in the binding pocket (Guo et al 2013;Xu et al 2016).…”
Section: Kai2 and D14 Are Both Receptor Proteins And Enzymesmentioning
confidence: 99%
“…Several studies have detected direct interaction between KAR 1 and KAI2 homologues using isothermal calorimetry and/or fluorescence-based binding assays (Guo et al 2013;Kagiyama et al 2013;Xu et al 2016). Two of these studies have also used crystallography to determine the position of KAR 1 in the binding pocket (Guo et al 2013;Xu et al 2016). However, each study revealed KAR 1 to sit in quite different orientations, perhaps because two different KAI2 proteins were investigated -one from Arabidopsis and one from the parasitic plant Striga hermonthica.…”
Section: Kai2 and D14 Are Both Receptor Proteins And Enzymesmentioning
confidence: 99%